Preventing mental strain for logistics workers: Guideline development - Patrick Schwarz; Matthias Klumpp (Data Science and Innovation in Supply Chain Management: How Data Transforms the Value Chain. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 29, 2020)
Purpose: The purpose of this paper is to discuss and analyze the introduction of a guideline, which aims to help prevent mental strain for logistics workers in an increasingly digitalized work environment. The guideline originates from the findings of computer science experimental rooms (IR) and expert workshops, which were analyzed in three German companies and are part of the INQA-project DIAMANT as well as from literature findings. Methodology: Mental strain and stress are identified from interviews and questionnaires in three experimental rooms as well as from literature review (and discussions with the logistics workforce of the German companies). The identified factors are then translated into a guideline with recommendations for reaching and maintaining a healthy digitalized work environment in logistics. Findings: The guideline "Case Studies Digitalization" shows the (interim) results of the three experimental rooms of the INQA-project DIAMANT. This paper offers insights regarding certain elements of the guideline and how the different recommendations were created. Originality: The paper provides interesting insights into the development process of a guideline that focuses on requirements for healthy digitalized work in logistics. Along with these requirements, the challenges today's logistics workforce faces in a quickly changing work environment are exposed.
urn:nbn:de:gbv:830-882.0115351; hdl:10419/228914; https://econpapers.repec.org/RePEc:zbw:hiclpr:29
Keywords: 650; Logistics; Industry 4.0; Digitalization; Innovation; Supply Chain Management; Artificial Intelligence; Data Science